Cyber-Security Incidents: A Review Cases In Cyber-Physical Systems - Al-Mhiqani, Mohammed Nasser Ahmed; Ahmad, Rabiah; S. M. M Yassin, S. M. Warusia Mohamed; Hassan, Aslinda; Zainal Abidin, Zaheera; Al-BaChaChee, Nabeel Salih Ali; Al-Aridhee, Karrar Hameed Abdulkareem (The Science And Information (SAI) Organization Limited, 2018)
Cyber-Physical Systems refer to systems that have an interaction between computers, communication channels and physical devices to solve a real-world problem. Towards industry 4.0 revolution, Cyber-Physical Systems currently become one of the main targets of hackers and any damage to them lead to high losses to a nation. According to valid resources, several cases reported involved security breaches on Cyber-Physical Systems. Understanding fundamental and theoretical concept of security in the digital world was discussed worldwide. Yet, security cases in regard to the cyber-physical system are still remaining less explored. In addition, limited tools were introduced to overcome security problems in Cyber-Physical System. To improve understanding and introduce a lot more security solutions for the cyber-physical system, the study on this matter is highly on demand. In this paper, we investigate the current threats on Cyber-Physical Systems and propose a classification and matrix for these threats, and conduct a simple statistical analysis of the collected data using a quantitative approach. We confirmed four components i.e., (the type of attack, impact, intention and incident categories) main contributor to threat taxonomy of Cyber-Physical Systems